2014
DOI: 10.1111/1467-9817.12037
|View full text |Cite
|
Sign up to set email alerts
|

Types and sequences of self‐regulated reading of low‐achieving adolescents in relation to reading task achievement

Abstract: This study examines the relationship between types and sequences of selfregulated reading activities in task-oriented reading with quality of task achievement of 51 low-achieving adolescents (Grade 8). The study used think aloud combined with video observations to analyse the students' approach of a content-area reading task in the stages of orientation, text reading and answering questions. Results show that in general these low-achieving adolescents are infrequently monitoring their text comprehension or mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…One of the students in the study stated that the instrument used in the study, SORS, was beneficial for her to become aware of the types of strategies to be used while reading academic materials. In addition to administering these kinds of instruments, self-regulated reading activities and strategy tips can be provided to learners in order to create awareness for employment of effective and appropriate strategies (de Milliano et al, 2014). Martinez (2008) pinpoints that if students are not aware of their own FL reading strategies, they cannot adopt effective strategies to deal with target language texts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the students in the study stated that the instrument used in the study, SORS, was beneficial for her to become aware of the types of strategies to be used while reading academic materials. In addition to administering these kinds of instruments, self-regulated reading activities and strategy tips can be provided to learners in order to create awareness for employment of effective and appropriate strategies (de Milliano et al, 2014). Martinez (2008) pinpoints that if students are not aware of their own FL reading strategies, they cannot adopt effective strategies to deal with target language texts.…”
Section: Resultsmentioning
confidence: 99%
“…While reading in the target language, FL learners use strategies to increase reading comprehension when they lack proficiency in reading (Mokhtari and Sheorey, 2002;Magogwe, 2013). Performance on a reading task or test may be an indicator of using effective and appropriate strategies (Phakiti, 2003;de Milliano et al, 2014) whereas learners who do well on general reading performance tests may fail to use effective reading strategies when they are reading academic materials (Mokhtari and Sheorey, 2002). Similarly, higher proficiency in a foreign language may not always be equal to effective strategy use and reading comprehension (Li and Munby, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have to consider the fact that our students were low-achievers and therefore may need much more guidance in group work than higher achieving students. Moreover, our students may need more support in comprehension monitoring as studies have shown that low-achievers are not used to making inferences and practicing other types of deeper comprehension processes (Oakhill & Cain, 2007;Rapp, Van den Broek, McMaster et al, 2007;De Milliano, Van Gelderen, Sleegers, 2014). Our own classroom observations of the treatment teachers do, suggest that the majority of them indeed experienced serious problems with group work guidance, resulting in insufficient collaborative practice in reading strategies in the whole-classroom settings.…”
Section: Difficulties In Finding Intervention Effects Of Reading-stramentioning
confidence: 88%
“…In addition, we have to consider the fact that our students were low-achievers and therefore may have needed much more guidance in group work than higher achieving students. Our students have to be supported in comprehension monitoring, because many of them are not used making inferences and practicing other types of deeper comprehension processes (Oakhill & Cain, 2007;Rapp, Van den Broek, McMaster et al, 2007;De Milliano, Van Gelderen, Sleegers, 2014).…”
Section: Group Workmentioning
confidence: 99%
See 1 more Smart Citation